A New IOL with Labeled Accurate Dioptric Powers Reduces the Postoperative Refractive Error - Wetterwald, N. (Klinische Monatsblätter für Augenheilkunde, 2014)
Background: There is a need for improved predictability in cataract surgery. The aim of this study was to investigate whether implantation of intraocular lenses (IOLs) with accurately labeled dioptric power could improve the postoperative results and allow better predictability. Patients and Methods: 113 eyes were implanted with Crystal Evolution® (MTO) IOLs and 261 eyes with AF-1 iMics1® (Hoya) IOLs. The predictability of the postoperative spherical equivalence (SE) and the best-corrected visual acuity (BCVA) were compared between both groups. The predictability was also compared to 2 previous studies. Results: With Crystal Evolution®, the predictability was significantly better than with AF-1 iMics1® (p < 0.0001). The results were also better than those described in the 2 studies. Although the BCVA obtained with Crystal Evolution® were better than with AF-1 iMics1®, the difference were not significant. Conclusions: Our data indicate that accurate dioptric labeling of IOLs may improve the postoperative refraction outcome.
Keywords: refraction predictability; dioptric labeling of IOLs; cataract surgery